Antioxidant and Antibacterial Activity of Yellow Wood (Coscinium fenestratum) Fruits Peel from East Kalimantan: Aktivitas Antioksidan dan Antibakteri Kulit Buah Kayu Kuning (Coscinium fenestratum) Asal Kalimantan Timur - Kustiawan, Paula Mariana; Arbainsyah, Arbainsyah; Setiawan, Irfan Muris (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Yellow wood (Coscinium fenestratum) is one of the typical forest plants of East Kalimantan. The hallmark of this plant is the roots, stems and the fruits pulp have a yellow color. There have been many studies on its use and potential in treating liver disease. However, there is limited research about the use of their fruits peel. Objectives: The purpose of this study was as an initial screening of the antioxidant and antibacterial activity from yellow wood (Coscinium fenestratum) fruits peel. Material and Methods: The yellow wood fruits peel was extracted using methanol solvent to obtain the MeOH extract of their fruits peel. The DPPH test was carried out to determined its antioxidant activity (25,50 and 100 ppm). The agar well difusion method was carried out to determined its antibacterial activity. Phytochemical tests are also carried out to determined the secondary metabolites of that fruits peel. Results: The results of the phytochemical test showed that the fruits peel contained alkaloids, flavonoids, carbohydrates, and tannins, but there were no terpenoids or steroids. The fruits peel has an antioxidant activity (58%) at 100 ppm concentration. While the antibacterial test showed strong inhibition at 100 ppm concentration on S. mutans, S. aureus, P. acne and E. coli bacteria. Conclusions: The fruits peel of the yellow wood has compounds that have strong antibacterial activity and medium antioxidant activity.